More Than Servants of the State? The Governance of Initial Teacher Preparation in Canada in an Era of School Reform (Alberta Journal of Educational Research, 2010)
Drawing on Gideonse’s (1993) distinction between political, institutional, and professional modes of governance, this article examines changes in the governance of initial teacher preparation in Canada over the last three decades. With data collected from a review of provincial documents and key informant interviews, the article uses Quebec, Manitoba, and British Columbia as case studies to illustrate how provincial governments, universities and their faculties of education, and the teaching profession have been able to exert their influence on the preparation of teachers. The article argues that each of these players constitutes a legitimate partner in initial teacher education, that each partner brings to the governance of initial teacher education varied core values and interests, and that diverse provincial governance arrangements reflect varied accommodations of these values and interests that have implications for how teacher professionalism and teachers’ work is being constructed.